Railroad inspector for railroad department in Malaysia - Azuan, Ismail (2013)
This thesis is the design of an autonomous robot which this robot can detect defect on railroad to prevent the future accident. This final year project carry out by the author to fulfillment the requirement for award the degree of Bachelor Mechatronics Engineering. This designed robot which has two stages of development and included two models. The first model is for PSM 1 and the second is fully functional model is for PSM 2. Basically, the design of robot quite more interesting, modern, unique and environmental friendly which using Arduino Uno and Agilent Instrument as a platform. In this report, I had made entire analysis requirement, design circuit, check output and input data and other important parameters to realization the design of the working robot that can be implementation by railroad department. On the other hand, this report is to aim to provide objective and scope of the research, the literature review study, research methodology, and fabrication process with result analysis and conclusion as part requirement in submitted the report to PSM supervisor. Although railroad inspection and development is still new technology in Malaysia and nodomestic consumption in this technology, but through this project can help the industry a step further. It is because this project can categorized as successful and working as expected. Finally, I wish this project can categorized on research and design development by interesting mechatronics student.